2017
DOI: 10.1016/j.kjms.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography findings in Parkinson's disease

Abstract: The aim of this study is to compare optical coherence tomography (OCT) findings of retinal thickness (RT) and retinal nerve fiber layer thickness (RNFLT) of idiopathic Parkinson's disease (IPD) patients to those of healthy subjects, and to investigate whether there is any relationship between the severity of the disease and the RNFLT values. This prospective study was included 25 IPD patients and 29 healthy controls. In the IPD group, the Hoehn and Yahr (H&Y), Unified Parkinson's Disease Rating Scale (UPDRS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
(32 reference statements)
4
22
0
Order By: Relevance
“…The 36 studies were all published between 2011 and 2020. The flow diagram of the search procedure is shown in Figure 1 and the characteristics of the included studies are described in Table 1 [11,19–53]. Patients with PD had a mean age of 64.8 (53.4–74.61) years and a mean duration of 6.7 (0.675–18.44) years.…”
Section: Resultsmentioning
confidence: 99%
“…The 36 studies were all published between 2011 and 2020. The flow diagram of the search procedure is shown in Figure 1 and the characteristics of the included studies are described in Table 1 [11,19–53]. Patients with PD had a mean age of 64.8 (53.4–74.61) years and a mean duration of 6.7 (0.675–18.44) years.…”
Section: Resultsmentioning
confidence: 99%
“… 11 Similarly, another study found that toxic accumulation of iron, which is known to play a role in PD, was two-folds higher among patients with AMD compared to that of controls. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Significant thinning in global, superior, inferior, nasal and temporal pRNFL have been observed. 89,91,9397,99104,106,119 In contrast, several studies have reported no significant differences. 77,87,88,90,92,105 A total of 13 case-control studies were included in a meta-analysis, supporting pRNFL thinning in all four quadrants (WMD = 25.76, 95% CI: 28.99–22.53, p = 0.0005).…”
Section: Parkinson’s Diseasementioning
confidence: 90%